MENTAL HEALTH SERVICES DURING THE PANDEMIC: THE EXPERIENCES OF LITHUANIAN PSYCHOLOGISTS - Vaičekauskaitė, Rita; Babarskienė, Jurgita; Grubliauskienė, Jūratė (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
With the COVID-19 pandemic and its restrictions, many countries face an unprecedented mental health crisis, which is being addressed in various ways, including the use of remote mental health services. Lithuania faced two quarantines: in March-June of 2020 and starting November 2020 up to Spring of 2021. The aim of this study is to explore the experiences of Lithuanian psychologists providing mental health services during the pandemic. Using the qualitative content analysis method, the following categories were made: from shock to discovery of new opportunities (differences in two lockdowns, better accessibility of services, help-seeking during the pandemic, and the importance of self-care) and contextual challenges (confidentiality, computer literacy, and blurred home/work boundaries). Implications for addressing psychological service issues are discussed, with an emphasis on self-care, setting boundaries, and finding new ways to enhance mental health via mediated communication as well as to reach out to vulnerable groups.